Central bank independence in New Zealand: Public knowledge about and attitude towards the policy target agreement - Bernd Hayo; Florian Neumeier (Philipps-University Marburg, School of Business and Economics, 2018)
Employing unique representative survey data from New Zealand collected in 2016, we study public knowledge about and attitude towards a specific monetary policy institution, the Policy Target Agreement (PTA). The PTA contains the inflation target for the Reserve Bank of New Zealand (RBNZ). First, we assess how much the population knows about the PTA, finding the level of knowledge to be low. Second, we ask whether our respondents support a clause in the PTA that allows the government to over-ride the RBNZ if it deems it necessary. We interpret responses to that question as attitudes towards central bank independence (CBI). The population does not appear to have a clear view on whether or not to expand CBI, as roughly one third supports the overriding clause in the PTA, one third is against it, and one third is unsure. Using logit regression, we study which characteristics make people favour more CBI. Subjective and objective knowledge about the RBNZ and monetary policy increases support for CBI, whereas voting for a national-oriented party and trusting the government reduces it. Policy implications are derived from our findings.
Keywords: E42; E52; E58; Z1; 330; Central Bank Independence; Public Attitude; Policy Target Agreement; Economic Literacy; New Zealand; Monetary Policy; Household Survey